Answer:
the equation is true only if c=6 and d=2.
Explanation:
We have the following expression:
![\sqrt[3]{162x^(c)y^(5)} = 3x^(2)y\sqrt[3]{6y^(d)}](https://img.qammunity.org/2020/formulas/mathematics/college/zuywhd746ie0pypnkjbihw9mvqjv990d3i.png)
Elevating to the power of three:
![162x^(c)y^(5)=27x^(6)y^(3)(6y^(d))](https://img.qammunity.org/2020/formulas/mathematics/college/jdfmvnemzrj81v068x5543slbslfwg5shr.png)
Simplifying:
→
![162x^(c)y^(5)=162x^(6)y^(3)y^(d)](https://img.qammunity.org/2020/formulas/mathematics/college/nsrcv2i1wl7tyitxqqfvi6ocmp10mapfqp.png)
→
![x^(c)y^(5)=x^(6)y^(3)y^(d)](https://img.qammunity.org/2020/formulas/mathematics/college/ulpttsos0bssanx3u7prez3z24ze3sspsq.png)
→
![x^(c)y^(5)=x^(6)y^(d+3)](https://img.qammunity.org/2020/formulas/mathematics/college/f85jxfhow3lczzg2f3lnt8fnia8hqno25q.png)
By comparing the two expression, we can say that:
![c=6](https://img.qammunity.org/2020/formulas/mathematics/high-school/dj0go31z8c008y306g5k1wdyehka335vlm.png)
→
![d=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7fnzn8ig20in3pzwnj6vuxjd1zjjg3cum1.png)
Therefore, the equation is true only if c=6 and d=2.